2004
DOI: 10.1364/opex.12.002838
|View full text |Cite
|
Sign up to set email alerts
|

Spectral broadening of a partially coherent CW laser beam in single-mode optical fibers

Abstract: The nonlinear propagation of a partially coherent continuous-wave laser beam in single-mode optical fibers is investigated both theoretically and experimentally, with a special attention to the zero-dispersion wavelength region where modulation instability is expected. Broadband asymmetric spectral broadening is reported experimentally and found in fairly good agreement with a numerical Schrödinger simulation including a phase-diffusion model for the partially coherent beam. This model shows in addition that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(80 citation statements)
references
References 13 publications
5
75
0
Order By: Relevance
“…Besides, when DWs are radiated by fundamental solitons from higher-order soliton fission, a maximum of intensity should appear at the blue edge of the spectrum [30], [32], which is not our case. Instead, our results are consistent with theoretical predictions for which in CW-pumping regimes fundamental solitons of slightly different amplitude and time duration originate from phase noise of the pump due to MI [11], [12], [14]. Immediately after formation they release non-solitonic radiation in the presence of higherorder dispersion and continue to radiate some energy while Raman red-shifting until stability is reached.…”
Section: Anomalous Dispersion Regime and Dispersive Wave Generationsupporting
confidence: 91%
See 1 more Smart Citation
“…Besides, when DWs are radiated by fundamental solitons from higher-order soliton fission, a maximum of intensity should appear at the blue edge of the spectrum [30], [32], which is not our case. Instead, our results are consistent with theoretical predictions for which in CW-pumping regimes fundamental solitons of slightly different amplitude and time duration originate from phase noise of the pump due to MI [11], [12], [14]. Immediately after formation they release non-solitonic radiation in the presence of higherorder dispersion and continue to radiate some energy while Raman red-shifting until stability is reached.…”
Section: Anomalous Dispersion Regime and Dispersive Wave Generationsupporting
confidence: 91%
“…The process of converting a CW laser emission into supercontinuum in optical fibers has been studied intensively in the last years, both experimentally [5], [6], [7], [8], [9], [10] and theoretically [11], [12], [13], [14]. These studies have shown that CW SC sources are initiated by modulation instability (MI) of the partially coherent input beam, which can lead to soliton formation and collision processes [15], [14].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, MI spectra, with the width being inversely proportional to the secondorder dispersion, will be broadened, and it will no longer be possible to consider the dispersion over the whole spectral span to be constant. It will thus be necessary to account for the TOD term, as in other studies in nonlinear fiber optics related to MI [22,24,25] in the low-dispersion region of optical fibers.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
“…If the dispersion cannot be considered to be a constant over the spectrum, the TOD term must be taken into account [21][22][23][24][25][26][27][28]. This higher-order term strongly modifies the dynamics of nonlinear systems by making them convectively unstable [21].…”
Section: Introductionmentioning
confidence: 99%
“…Supercontinuum (SC) generation in optical fibers from continuous-wave (cw) laser has been studied intensively in the last years, both experimentally [1]- [9] and theoretically [10]- [12]. These broadband, high power density and low-coherence light sources have been found to be extremely useful for optical coherence tomography (OCT) [13], [14].…”
Section: Introductionmentioning
confidence: 99%